Penyusunan Informasi Kinerja dengan Pendekatan Logic Model dalam Perencanaan dan Penganggaran di Ombudsman Republik Indonesia - Astanto, Tri; Saleh, Choirul; Rozikin, Mochamad (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose of this research is revealing the process of preparation of performance information with logic model approach in planning and budgeting that exist at Ombudsman of The Republic of Indonesia and then which supporting factor and constrain. Furthermore, revealing the process in comprehensive ways, the researcher arrange it according to the stage of building a logic model created by Mclaughlin and Jordan (2015). The result of this research indicated that most of preparation of performance information stage are according to the stage of building a logic model, however there are crucial finding that has not same/ accordance to which are some stage that not done (model drawing stage and the involvement of key stakeholders). This paper only potrait the current condition of Ombudsman of The Republic of Indonesia that it is not proper for other institutions. However, the potrait of process and supporting factor condition and constrain could be the reference of makes research.